Religion and Politics in Contrast and Complementarity - John B Chethimattam (Journal of Dharma, 1982)
THE CRISIS Today the human race is facing a crisis more serious than any it has encountered in the past. because its very survival is in danger. In all ages there were prophets of doom. Though most often they spoke with personal conviction. their focus was on particular contexts and circumscribed issues. But today’s prophets speak with scientific authority. and the facts they present involve the whole human race and the planet earth itself. Today mankind is caught up in a storm of crisis. problems. and the ever accelerating pace of change leave little time to think calmly and clearly. Human extinction through nuclear and biological warfare appears a distinct possibility. As Aurelio Pecci states in his Chasm Ahead’. "Mankind is galloping in the direction of assured and possibly tota I disaster." Hence this is a situation in which all the different branches of knowledge should focus attention on the future of man on earth. Here politics and religion represent two poles of the human search for finding a way out of the present situation of crisis, one immediate and practical, the other transcendental and far-reaching. Politics which studies the utilization and organization of the various available immediate resources for the common good has to work with a clear model of future humanity in mind. Religion, on the other hand. dealing with the ultimate meaning and concerns of human life must show how those values can be made secure not only for present day population but for future generations as well. This article will briefly examine how different models and program- mes of the political society have deep religious implications and demand. therefore. a close collaboration with religions in their com- mon search for the good of the whole man.